Negosiasi Identitas Budaya Jepang dalam Novel Tenki No Ko dan Terjemahannya dalam Bahasa Indonesia - Fatin, Jihan Salsa Biela; Cholsy, Hayatul (Universitas Diponegoro, 2022)
The translator as a negotiator must ensure that all information contained in the source language text is conveyed to the target language reader. Because translation can be a way to overcome intercultural gaps. This study uses a qualitative descriptive method to find the formulation of the translation of Japanese cultural terms that have been negotiated in Indonesian translation. The material objects of this research were the Japanese novel 'Tenki No Ko' and its Indonesian translation 'Weathering With You’. The frameworks for this study were Newmark's cultural terms categorizations, Eco's idea of negotiation, and Baker's strategies for culture-specific items. This study revealed that the negotiation of Japanese cultural identity can be identified and formulated through the translation strategy used by the translator. The strategies were using general words, omissions, paraphrasing with related words, using neutral words, and using unrelated words. <a href=